Economic Impact of Water Harvesting Structures on Farmers of North Saurashtra Agro-climatic Zone - Biren Tilala; R. L. Shiyani (Journal of Agricultural Extension Management, 2025)
India is endowed with vast natural resources. Efficient and sustainable use of natural resources is necessary for economic development, especially, in the agricultural dominated economies like India. India’s agricultural production in general and food security in particular is critically dependent on the irrigation facilities created and their performance. Irrigation adds a very high value to the land, increases employment and income in the rural areas. Since irrigation is important for the development of agriculture and the nation’s food security, Indian Planners have given high priority to its development and proper utilization. Thus, the irrigation is the crucial input in attaining sustained agricultural development, and importance of irrigation in crop production as well as increasing agricultural productivity has been widely recognized all over the world and same has been clearly brought out by the micro- and macro-level studies in India (Dhawan, 1988; Shah, 1989; Vaidyanathan et al, 1994; Vekariya, 1997, Narayanamoorthy, 2001 and Palanichamy et al, 2002). But irrigated agriculture in India has probably reached its limit and further sustainable increase in food production must come from dry land farming, especially through harvesting of rainwater and its management. Construction of water harvesting structures is, therefore, given due priority by various state governments and non-government organizations (NGOs)